Assessment of the Nutritional Status of Adult Patients with Asthma - Mohamed, Mohamed Saleh (Pakistan Journal of Nutrition, 2008)
The present study was carried out on 120 adult patients (sixty male and sixty female) age 42.6 ± 1.8 years, they were selected from outpatient clinics of Tanta University Hospital, Egypt. All patients were diagnosed according to standard medical criteria as being asthmatic. Data for socioeconomic status, health history, anthropometric measurements and food habits were obtained. The 24 hour recall for three days was used for assessment of food intakes. Also, Hb, PCV, erythrocyte, leucocyte, eosinophil and lymphocytes counts and IgE were determined. The results revealed that the majority of males and females were diagnosed as having asthma because of chest allergy (50.0% and 60.0% respectively) and suffered daily asthma attacks (75.0% and 70.0% respectively). Most of the females and males had food allergy (65.0% and 75.0% respectively) particularly to eggs and fish. According to BMI, the majority of females and males were obese (55.0% and 60.0% respectively). Although mean Hb levels for the males was significantly (P